Make and solve the given equation d^{3} frac{y}{dx^{3}} - d^{2} frac{y}{dx^{2}}=2x + 3

Question
Differential equations
asked 2020-12-15
Make and solve the given equation \(d^{3}\ \frac{y}{dx^{3}}\ -\ d^{2}\ \frac{y}{dx^{2}}=2x\ +\ 3\)

Answers (1)

2020-12-16
Given \(d^{3}\ \frac{y}{dx^{3}}\ -\ d^{2}\ \frac{y}{dx^{2}} = 2x\ +\ 3\)
The above equation can be written as \((D^{3}\ -\ D^{2})y = 2x\ +\ 3\)
Now the auxiliary equation is \(m^{3}\ -\ m^{2} = 0\)
which gives \(m = 0,\ 0,\ 1\)
Hence the complimentary function is \(C.F. = C_{1}\ +\ C_{2}x\ +\ c_{3}e^{x}\)
Now we need to find the Particular Integral
\(y_{p}=\frac{1}{D^{2}\ +\ 3D\ -\ 10}x(x^{x}\ +\ 1)=\frac{1}{(D\ +\ 5)(D\ -\ 2)}xe^{x}\ +\ 1\)
\(=e^{x}\frac{1}{(D\ +\ 1\ +\ 5)(D\ +\ 1\ -\ 2)}x\ +\ \frac{1}{(D\ +\ 5)(D\ -\ 2)}x\)
\(=e^{x}\frac{1}{(D\ +\ 6)(D\ -\ 1)}x\ +\ \frac{1}{(D\ +\ 5)(D\ -\ 2)}x\)
\(=e^{x}\frac{1}{-6\left(1\ +\ \frac{D}{6}\right)(1\ -\ D)}x\ +\ \frac{1}{-10\left(1\ +\ \frac{D}{5}\right)\left(1\ -\ \frac{D}{2}\right)}x\)
\(=\ -\frac{e^{x}}{6}\left(1\ +\ \frac{D}{6}\right)^{-1}(1\ -\ D)^{-1}x\ -\ \frac{1}{10}\left(1\ -\ \frac{D}{5}\right)^{-1}\left(1\ -\ \frac{D}{2}\right)^{-1}xSK
\(=\ -\ \frac{e^{x}}{6}\left(1\ +\ \frac{D}{6}\ +\ \cdots\right)(1\ +\ D\ +\ D^{2})x\ -\ \frac{1}{10}\left(1\ +\ \frac{D}{5}\ \cdots\right)\left(1\ +\ \frac{D}{2}\ +\ \cdots\right)x\)
\(=\ -\ \frac{e^{x}}{6}\left(x\ +\ 1\ +\ \frac{1}{6}\right)\ -\ \frac{1}{10}\left(x\ +\ \frac{1}{5}\ +\ \frac{1}{2}\right)\)
\(=\ -\ \frac{e^{x}}{6}\left(x\ +\ \frac{7}{6}\right)\ -\ \frac{1}{10}\left(x\ +\ \frac{7}{10}\right)\)
Hence the general solution is
\(y=y_{c}\ +\ y_{p}=C_{1}e^{-5}x\ +\ C_{2}e^{2}x\ \pm\ e_{6}\left(x\ +\ \frac{7}{6}\right)\ -\ \frac{1}{10}\left(x\ +\ \frac{7}{10}\right)\)
0

Relevant Questions

asked 2021-02-26
Make and solve the given equation \(x\ dx\ +\ y\ dy=a^{2}\frac{x\ dy\ -\ y\ dx}{x^{2}\ +\ y^{2}}\)
asked 2020-12-05
Give the correct answer and solve the given equation:
\(\displaystyle{x}{y}{\left.{d}{x}\right.}-{\left({y}+{2}\right)}{\left.{d}{y}\right.}={0}\)
asked 2020-11-08
Make and solve the given equation \(x′′ − x′ = 6 + e^{2}t\)
asked 2021-02-21
Solve the given system of differential equations.
\[Dx+Dy+(D+1)z=0\)
Dx+y=e^{t}\)
Dx+y-2z=50\sin(2t)\)
asked 2021-02-20
Find the general solution to the equation \(\displaystyle{x}{\left(\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}\right)}+{3}{\left({y}+{x}^{2}\right)}=\frac{{ \sin{{x}}}}{{x}}\)
asked 2021-02-15
Solve
\(\left(d^{2}\frac{y}{dt^{2}}\right)\ +\ 7\left(\frac{dy}{dt}\right)\ +\ 10y=4te^{-3}t\) with
\(y(0)=0,\ y'(0)=\ -1\)
asked 2021-02-25
Give the correct answer and solve the given equation: \(\displaystyle{y}\ \text{ - 4y}+{3}{y}={x},{y}_{{1}}={e}^{x}\)
asked 2020-10-26
Find the differential dy for the given values of x and dx. \(y=\frac{e^x}{10},x=0,dx=0.1\)
asked 2021-01-02
Solve the Differential equations
\(\displaystyle{\frac{{{\left({d}^{{{2}}}\right)}{y}}}{\rbrace}}{\left\lbrace{d}{\left({t}^{{{2}}}\right\rbrace}+{4}{\left({\frac{{{\left.{d}{y}\right.}}}{{{\left.{d}{t}\right.}}}}+{3}{y}={e}^{{-{t}}}\right.}\right.}\)
asked 2020-11-22
Deterrmine the first derivative \(\displaystyle{\left(\frac{{\left.{d}{y}\right.}}{{\left.{d}{x}\right.}}\right)}\) :
\(\displaystyle{y}={2}{e}^{{2}}{x}+{I}{n}{x}^{{3}}-{2}{e}^{{x}}\)
...